The New Prevention of Terrorism Act 2015 (POTA): A Legal Comment - Kwang, Ho Peng (Journal of Malaysian and Comparative Law, 2018)
On April 7, 2015, our Parliament passed the new Prevention of Terrorism Act 2015 (POTA) after going through heated debate for more than 10 hours. The new POTA faced considerable opposition and criticism for introducing the continuing detention without trial, which the lawmakers have claimed to be similar to the already repealed Internal Security Act (ISA) that dominated Malaysia for the past 52 years. It was further contended by many quarters that the new POTA gives our government greater authority to track and intercept terrorist acts and the fear of it being abused is not guaranteed, judging from the past history of cases under preventive detention in Malaysia. Although our Prime Minister himself has given his assurance that the executive arm will not have any say on who to detain under POTA, nevertheless it creates new crimes, new penalties, and new procedures for use. The introduction of POTA by our government has also attracted adverse comments by Human Rights Watch Deputy Director Phil Robertson with the following remarks: “ by restoring indefinite detention without trial, Malaysia has re-opened Pandora’s box for politically motivated, abusive state actions”. Thus, it is the aim of this article to provide an assessment and legal commentary on the relevant sections of the POTA that are claimed to be ‘controversial’ by many, and whether it undermines basic human rights besides looking at other nations as a comparative study.